Running demands and activity profile of men’s rugby sevens: a tournament scenario - Lee, Marcus; Soo, Jacky; Yeo, Vincent; Rashid Aziz, Abdul; Ihsan, Mohammed (Biology of Sport, 2022)
This study profiled the changes in running performances and collisions within a Rugby sevens tournament. Sixteen male players were equipped with global positioning system units while competing at the 2015 and 2016 Asia Rugby Sevens series held in Colombo and Hong Kong, respectively. Both tournaments consisted of 4 matches each, and were played over 2 days (i.e., 2 matches/day). Total distance (TD) covered increased in match 3 compared with matches 1 (19 ± 19%; p < 0.001) and 2 (16 ± 11%; p = 0.001), whilst a decrease in TD in match 4 compared with match 3 (8 ± 9%; p = 0.019) was observed. Distances covered within 6.1–12 km·h-1 and 12.1–14 km·h-1 speed bands were generally higher in matches 3 and/or 4 when compared with match 1 and/or 2 (p < 0.05). Frequency of entries into 14.1–18 km·h-1 speed zone was decreased in match 4 compared with match 3 (45 ± 41%; p = 0.009), whilst incidences of heavy, very heavy and severe collisions were generally higher in matches 3 or 4 compared with matches 1 or 2 (p < 0.05). In conclusion, while some decrements in the final match were evident, running performance were generally maintained throughout despite the competitive and congested nature of Rugby Sevens tournaments.